Improved Psychosocial and Functional Outcomes and Reduced Opioid Usage Following Burst Spinal Cord Stimulation. Issue 3 (25th June 2020) - Falowski, Steven M.; Moore, Gregory A.; Cornidez, Eric G.; Hutcheson, J. Kelby; Candido, Kenneth; Peña, Isaac; Blomme, Bram; Capobianco, Robyn A.
Abstract: Objective: Burst spinal cord stimulation (B‐SCS) has been shown to reduce neuronal firing in the anterior cingulate cortex through selective modulation of the medial pain pathway tract. This pain pathway communicates the affective component of pain processing. The purpose of this study was to assess the effect of B‐SCS on psychosocial functioning and its influence on pain and quality of life. Materials and Methods: Eligible patients with chronic, intractable pain of the trunk, and/or lower limbs were enrolled. After a successful trial period, subjects received a permanent implant and returned for follow‐up at 6‐ and 12‐months. Results: In total, 269 patients were enrolled at 22 centers. Trial success rate was 90%. Significant improvements in pain, physical, mental, and emotional functioning were observed from baseline to the 6‐ and 12‐month follow‐up ( p  < 0.001). Overall, patients had improved quality of life, became more active, and the negative impact of pain on daily life was decreasing. At one year, 81% of subjects were satisfied or very satisfied with their therapy. Subjects showing significant improvements on mental health outcomes reported enhanced pain relief and quality of life scores compared with subjects with continued impaired mental health at follow‐up. At one year, 89% of subjects who were taking opioids at baseline decreased or stayed at the same level of opioid use; 19% stopped taking any opioids. No unanticipated adverse events have been reported. Conclusions: One‐year outcomes after B‐SCS show improvements across all evaluated psychological measures with the largest impact observed on catastrophizing and depression (the affective component of pain processing). These pain‐related beliefs and behaviors, and not pain intensity, have been shown to put patients at greatest risk of a poor prognosis and quality of life.